Peran Penyuluh Pertanian dan Tingkat Pemberdayaan Petani Holtikultura di Desa Layeni Kecamatan Teon Nila Serua - Latuheru, Joseph; Sahusilawane, Aphrodite M; Far Far, Risyart A (Jurnal Agrosilvopasture-Tech, 2025)
This study aims to analyze the role of extension workers in Layeni Village. This study uses a qualitative descriptive research approach. This research was conducted in Layeni Village, Teon Nila District. The sample in this study was 40 respondents. The data collection techniques used in the study were questionnaires, observations, and documentation, with data analysis used, namely, qualitative descriptive data analysis and simple statistics. The results of the study showed that 1) The role of extension workers as facilitators was 24 respondents (60%), the role of extension workers as marketing partners was 25 respondents (62.5%), and the role of extension workers as motivators was 25 respondents (62.5%). 2) The level of farmer empowerment based on the indicator of the level of farmer's ability to obtain information was in the moderate category, namely 26 respondents (65%), then the level of farmer empowerment in the level of farmer's ability to make decisions was in the moderate category, namely 27 respondents (67.5)% and the last at the level of farmer's ability to partner was in the moderate category, namely 28 respondents (70%).